Analisis Mutu Hasil Gabah dan Beras Padi Gogo Aromatik Varietas Inpago Unsoed 1 - Siti Hasdiyanti Ramadhani; Ni Luh Sri Suryaningsih; Yosefina Mangera (Universitas Musamus, Merauke, Papua, 2018)
The purpose of the study was to determine the quality of the grainand rice are planted, the ricevarieties Inpago Unsoed 1. The research method use dis data collection, namely primary data andsecondary data. Primary data is used for observed in this research about grain moisturecontent,density of grain, foreign bodies, empty grains, grain crackedor broken, after the percentage ofgrain milled head of rice, broken rice, graing roats, grain limestone, yolk broken and milled rice yield.The results showed that during the observation the quality of grain varieties Inpago Unsoed 1 hasmilled at about 13,33% moisture content, grain density of 0,57g/ml, and grain weight is 27,60g/1000grain. The percentage point for the determination quality of head point is 73,49%, broken grainsabout 13,92%, and 12,34% graing roats. The quality of rice milled varieties inpago Unsoed 1 includelow. The lower of rice quality is due to the low of head rice percentage, while the percentage ofbroken grain sand high graing roats. Rice milled yield about 51,23%